2021
DOI: 10.3389/fneur.2021.648588
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlations in Monogenic Parkinson Disease: A Review on Clinical and Molecular Findings

Abstract: Parkinson disease (PD) is a complex neurodegenerative disorder, usually with multifactorial etiology. It is characterized by prominent movement disorders and non-motor symptoms. Movement disorders commonly include bradykinesia, rigidity, and resting tremor. Non-motor symptoms can include behavior disorders, sleep disturbances, hyposmia, cognitive impairment, and depression. A fraction of PD cases instead is due to Parkinsonian conditions with Mendelian inheritance. The study of the genetic causes of these phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 208 publications
1
66
1
Order By: Relevance
“…In addition, the aforementioned rheumatological deformity of the fingers and hands favours said difficulty in using devices for cutting nails, as well as the tremor present in the extremities. 9,[26][27][28][29] Regarding the results obtained in our study in the pain dimension, the patients with Parkinson's reported having discomfort and moderate pain to a greater extent than the healthy participants, although this result did not show statistically significant differences between the two groups. Previous studies highlight the issue of suffering from pain in Parkinson's patients.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, the aforementioned rheumatological deformity of the fingers and hands favours said difficulty in using devices for cutting nails, as well as the tremor present in the extremities. 9,[26][27][28][29] Regarding the results obtained in our study in the pain dimension, the patients with Parkinson's reported having discomfort and moderate pain to a greater extent than the healthy participants, although this result did not show statistically significant differences between the two groups. Previous studies highlight the issue of suffering from pain in Parkinson's patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Tremor-dominant/mixed/akinetic-rigid subtypes Predominant motor symptoms and generally a milder progression of motor and non-motor manifestations (including cognitive deterioration) (Mirelman et al, 2013;Marras et al, 2016;Trinh et al, 2018;Guadagnolo et al, 2021). The p.Arg1441Gly variant is manifested at the disease onset as a TD PD subtype in most patients, followed by an AR subtype (a quarter of patients), progression is slow, and dementia risk is low (Vinagre-Aragón et al, 2021).…”
Section: Number Of Subtypesmentioning
confidence: 99%
“…Monogenic forms of Parkinson's disease predominantly presenting with akinetic-rigid subtype PRKN Mutations in the PRKN (Parkin) are the most common cause of EOPD, responsible for up to 15% of all PD cases with onset below 50 years old (Guadagnolo et al, 2021;Jia et al, 2022;Dulski et al, forthcoming). They are inherited in an autosomal recessive manner.…”
Section: Number Of Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides SNCA , additional well-established genes are linked with monogenic forms of the disease: autosomal dominant PD is caused by mutations in leucine-rich repeat kinase 2 ( LRRK2 / PARK8 ) and vacuolar sorting protein 35 ( VPS35 / PARK17 ) genes, whereas mutations in PRKN ( Parkin / PARK2 ), PTEN-induced putative kinase 1 ( PINK1 / PARK6 ) and protein deglycase ( DJ-1 / PARK7 ) genes are associated with autosomal recessive PD [ 18 , 24 ]. In contrast to SNCA mutations that are rare, pathogenic variants detected in LRKK2 gene represent the most commonly frequent causes of PD, with an estimated frequency of 5% and 1% in familial and sporadic cases, respectively [ 25 , 26 ].…”
Section: The Genetic Landscape Of Parkinson’s Disease: a Brief Overviewmentioning
confidence: 99%